Reflections on “Reviving Confucian Culture” to Solve the Current Moral Decline in China - Yi Ren, Gao Peng (Forest Chemicals Review)
In this paper, the author has first made a dialectical analysis of the phenomenon of moral decline in current China, and analyzed its causes from China’s history and reality. Subsequently, the author has also analyzed the performance, essence and influence of the current “revival of Confucian culture” in current China. Therefore, the author has held that “reviving Confucian culture” can’t solve the current moral decline. Finally, combined with the social reality, the author has given some thoughts on its countermeasures.